A new evaluation method for +Gz tolerance with loratadine by using a near-infrared spectroscopy - Onozawa, Akihiko; Kikukawa, Azusa; Miyamoto, Yoshinori (Dynamic medicine DM, 2008)
Background Loratadine (Claritin ® ), an over the counter antihistamine in U.S. and UK, is acceptable for use without adverse side effects by aircrew with mild or moderate allergic or other situations requiring an antihistamine. Although +Gz (head to foot direction) tolerance testing for aircrew with loratadine has not been documented in the published literature, it is commonly accepted that loratadine dose not effect +Gz tolerance. The purpose of this study was to offer and validate a new evaluation method for +Gz tolerance testing with loratadine by using a near-infrared spectroscopy (NIRS). Methods A double-blind, placebo-controlled, randomized, crossover protocol was used to administer 10 mg of loratadine or placebo in nine healthy subjects. The subjects didn't wear anti-G suit. The +Gz exposure profiles consisted of, in series, a gradual onset ran (0.1 G·sec -1 ) to the subject's visual end-point (peripheral light loss) or loss of consciousness (GLOC), and rapid onset run (1.0 G·sec -1 ) to the subject's same end-point. In this study, G-level tolerance was defined as the +Gz level at visual end-point and/or at GLOC. As a subject's G-duration tolerance, we measured the total time (seconds) during rapid onset run. Otherwise, to confirm the effect of loratadine on +Gz tolerance, we measured the cerebral NIRS variables (hemoglobin concentration changes and tissue oxygenation index) as a new quantitative method for +Gz tolerance during a centrifuge experiments. Results No significant differences were observed in +Gz tolerance (+Gz level, duration time and NIRS variables) between subjects taking loratadine and placebo. Conclusion Our results demonstrate that loratadine has no detectable effect on +Gz tolerance by using a new method with cerebral NIRS variables and the traditional method with +Gz level and duration time. This study represents the first use of a quantitative parameter such as cerebral NIRS variables to assess the effects of a drug on acceleration tolerance.